Negative electrode and secondary battery including the same
By using negative electrode active material particles with appropriate particle size distribution and specific surface area, including natural graphite and carbon coatings, the problems of natural graphite volume expansion and electrolyte side reactions during charging/discharge are solved, and the rapid charging of the battery is achieved Improved performance and lifespan.
Patent Information
- Application Number
- CN202080007724.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-01-14
- Filing Date
- 2020-01-14
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2040-01-14
AI Technical Summary
The prior art is difficult to effectively control the volume expansion of natural graphite and electrolyte side reactions of secondary batteries during charging/discharging, resulting in poor fast charging and life performance of the battery.
Using negative electrode active material particles with appropriate particle size distribution and specific surface area, including natural graphite and carbon coatings, improve current transfer and lithium ion embedding/deintercalation efficiency by reducing stress inside the negative electrode active material particles and controlling internal pores.
It effectively reduces the volume expansion degree of natural graphite in the negative electrode active material particles, and improves the fast charging performance and life performance of the battery.
Smart Images

Figure CN113614950B_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2019-0004798 filed on January 14, 2019, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0004] The present invention relates to a negative electrode and a secondary battery comprising the negative electrode, wherein the negative electrode comprises a current collector and a negative electrode active material layer, wherein the negative electrode active material layer comprises negative electrode active material particles, the negative electrode active material particles comprise natural graphite and a carbon coating disposed on the natural graphite, and in terms of particle size distribution, the negative electrode active material particles have a D of 6 μm to 9.2 μm. 50 and a half width of 5.0 μm to 5.5 μm, and the specific surface area of the negative electrode active material particles is 0.6 m 2 / g to 2.2m 2 / g. Background Art
[0005] As the use of fossil fuels has increased rapidly, there is an increasing demand for the use of alternative or clean energy, and as part of this trend, the most actively researched field is the field of power generation and storage using electrochemical reactions.
[0006] At present, a typical example of an electrochemical device using such electrochemical energy is a secondary battery and its field of use is becoming larger and larger. In recent years, with the increase in technological development and demand for portable devices such as portable computers, mobile phones and cameras, the demand for secondary batteries as energy sources has increased significantly. Generally, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte and a separator. The negative electrode contains a negative electrode active material for embedding and de-embedding lithium ions from the positive electrode, and as the negative electrode active material, a graphite-based active material, such as natural graphite or artificial graphite, can be used.
[0007] As the charging and discharging of the battery continues, the volume of natural graphite expands, thereby deteriorating the life performance of the battery. Generally, in order to control the volume expansion, a carbon coating has been provided on natural graphite. However, it is difficult to reduce the stress inside the natural graphite by using only the carbon coating, and the area in which the electrolyte side reaction occurs cannot be fully controlled, thereby limiting the control of the volume expansion.
[0008] Therefore, a new method capable of effectively controlling the volume expansion of natural graphite during charge / discharge of a battery is needed. Summary of the invention
[0009] Technical issues
[0010] One aspect of the present invention provides a negative electrode and a secondary battery including the same, the negative electrode being capable of improving fast charging performance and life performance of a battery by effectively controlling volume expansion of natural graphite and electrolyte side reactions when the battery is charged and discharged.
[0011] Technical Solution
[0012] According to one aspect of the present invention, a negative electrode is provided, the negative electrode comprising a current collector and a negative electrode active material layer, wherein the negative electrode active material layer comprises negative electrode active material particles, the negative electrode active material particles comprise natural graphite and a carbon coating disposed on the natural graphite, and in terms of particle size distribution, the negative electrode active material particles have a D of 6 μm to 9.2 μm. 50 and a half width of 5.0 μm to 5.5 μm, and the specific surface area of the negative electrode active material particles is 0.6 m 2 / g to 2.2m 2 / g.
[0013] According to another aspect of the present invention, a secondary battery including the negative electrode is provided.
[0014] Beneficial Effects
[0015] According to the present invention, negative electrode active material particles with suitable size are used, so that the stress inside the negative electrode active material particles can be reduced. Therefore, during the charging and discharging of the battery, the volume expansion degree of natural graphite in the negative electrode active material particles can be reduced. In addition, since negative electrode active material particles with suitable half width in particle size distribution are used, the current can be uniformly transmitted to the negative electrode, so that the problem of lithium precipitation in a specific part that is prone to occur can be reduced. Therefore, the fast charging performance of the battery can be improved. In addition, since the internal pores are controlled so that negative electrode active material particles with low specific surface area are used, the volume expansion of natural graphite in the negative electrode active material particles can be further controlled. By controlling the volume expansion, the life performance of the battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a graph showing the particle size distribution of negative electrode active material particles used in each of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3; and
[0017] Figure 2 : is a graph showing the voltage change when the battery manufactured by using each of the negative electrodes of Example 1 and Comparative Example 1 is charged. DETAILED DESCRIPTION
[0018] Hereinafter, the present invention will be described in more detail to facilitate understanding of the present invention.
[0019] It should be understood that the words or terms used in this specification and claims should not be interpreted as having the meanings defined in commonly used dictionaries. It will be further understood that the words or terms should be interpreted as having the meanings consistent with their meanings in the context of the relevant art and the technical concept of the present invention based on the principle that the inventor can appropriately define the meanings of the words or terms to best explain the present invention.
[0020] The terminology used herein is for the purpose of describing particular exemplary embodiments only and is not intended to be limiting of the present invention. Terms in the singular may include plural forms unless the context clearly indicates otherwise.
[0021] In the present specification, it should be understood that the terms "include", "comprises" or "has" are intended to specify the presence of stated features, numbers, steps, elements or a combination thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements or a combination thereof.
[0022] In this manual, D 10 , D 50 and D 90 The D can be defined as the particle sizes corresponding to 10%, 50% and 90% of the cumulative volume in the particle size distribution curve, respectively. 10 , D 50 and D 90 The particle size can be measured, for example, by laser diffraction, which is generally capable of measuring particle sizes from the submicron region to several millimeters, thereby obtaining highly reproducible and high-resolution results.
[0023] In this specification, the specific surface area (specifically the specific surface area of the negative electrode active material particles) can be measured by the Brunauer-Emmett-Teller (BET) method. For example, using a porosimetry analyzer (Bell Japan Inc., Belsorp-II mini), the specific surface area can be measured by a nitrogen adsorption / distribution method, by a BET 6-point method.
[0024] In the present specification, the pore volume (particularly the pore volume of the negative electrode active material particles) can be measured by a porosimetry analyzer (Bell Japan Co., Ltd., Belsorp-II mini).
[0025] In the present specification, the tap density may be a density calculated by placing 40 g of negative electrode active material particles in a container and tapping it 1000 times.
[0026] <Negative electrode>
[0027] The negative electrode according to one embodiment of the present invention may include a current collector and a negative electrode active material layer, wherein the negative electrode active material layer includes negative electrode active material particles, the negative electrode active material particles include natural graphite and a carbon coating disposed on the natural graphite, and in terms of particle size distribution, the negative electrode active material particles have a D of 6 μm to 9.2 μm. 50 and a half width of 5.0 μm to 5.5 μm, and the specific surface area of the negative electrode active material particles is 0.6 m 2 / g to 2.2m 2 / g.
[0028] The current collector is not particularly limited as long as it has conductivity without causing chemical changes in the battery. For example, as the current collector, copper, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. Specifically, transition metals such as copper and nickel that adsorb carbon well can be used as the current collector. The thickness of the current collector can be 6 μm to 20 μm, but the thickness of the current collector is not limited thereto.
[0029] The negative electrode active material layer may be disposed on the current collector. The negative electrode active material layer may be disposed on at least one surface of the current collector, specifically, on one surface or both surfaces thereof.
[0030] The negative electrode active material layer may include negative electrode active material particles.
[0031] The negative electrode active material particles may include natural graphite and a carbon coating.
[0032] Since natural graphite is included in the negative electrode active material particles, the capacity of the battery can be improved.
[0033] The natural graphite may be a spherical or nearly spherical natural graphite formed by modifying flaky natural graphite particles. Specifically, the natural graphite may be formed by agglomerating flaky natural graphite particles. More specifically, the natural graphite may be formed by rolling or abrading flaky natural graphite particles via a mechanical process. Therefore, when observing the interior of the natural graphite, a boundary surface may be present therein, indicating that the flaky natural graphite has aggregated.
[0034] The natural graphite may have an average particle size (D 50 ). When the above range is satisfied, volume expansion of the negative electrode during charge / discharge of the battery can be suppressed.
[0035] The carbon coating layer may include at least any one of amorphous carbon and crystalline carbon.
[0036] The crystalline carbon may further improve the electrical conductivity of the natural graphite.The crystalline carbon may include at least any one selected from the group consisting of fluorene, carbon nanotubes, and graphene.
[0037] The amorphous carbon can appropriately maintain the strength of the coating layer, thereby suppressing the expansion of natural graphite. The amorphous carbon can be at least any one carbide selected from the group consisting of tar, pitch and other organic materials, or a carbon-based material formed by using hydrocarbons as a chemical vapor deposition source.
[0038] The carbide of the other organic material may be a carbide of an organic material selected from the group consisting of carbides of sucrose, glucose, galactose, fructose, lactose, mannose, ribose, aldohexose or ketohexose, and a combination thereof.
[0039] The hydrocarbon may be a substituted or unsubstituted aliphatic hydrocarbon or alicyclic hydrocarbon, or a substituted or unsubstituted aromatic hydrocarbon. The aliphatic hydrocarbon or alicyclic hydrocarbon in the substituted or unsubstituted aliphatic hydrocarbon or alicyclic hydrocarbon may be methane, ethylene, ethylene, acetylene, propylene, butane, butene, pentene, isobutylene or hexane, etc. The aromatic hydrocarbon in the substituted or unsubstituted aromatic hydrocarbon may be benzene, toluene, xylene, styrene, ethylbenzene, diphenylmethane, naphthalene, phenol, cresol, nitrobenzene, chlorobenzene, indene, coumarone, pyridine, anthracene or phenanthrene, etc.
[0040] The carbon coating layer may be contained in the negative electrode active material particles in an amount of 1 wt % to 15 wt %, specifically 2 wt % to 10 wt %, and more specifically 3 wt % to 7 wt %. When the above range is met, the specific surface area of the negative electrode active material particles is reduced, so that the side reaction of the negative electrode active material particles and the electrolyte can be reduced and the excessive volume expansion of the negative electrode can be suppressed.
[0041] In terms of particle size distribution, the negative electrode active material particles may have a particle size distribution of 6 μm to 9.2 μm, specifically 7 μm to 9.2 μm, and more specifically 8 μm to 9.1 μm. 50 When the above range is met, it means that the particle size of the natural graphite in the negative electrode active material particles is small, and further, it means that the size of the flaky natural graphite particles constituting the natural graphite is small. Therefore, when the above range is met, during the charge / discharge of the battery, the internal stress of the negative electrode active material particles, specifically the natural graphite, can be easily reduced, thereby suppressing the volume expansion of the negative electrode active material particles.
[0042] Specifically, when the negative electrode active material particles have a D 50When the negative electrode active material particles have a D of greater than 9.2 μm, it is difficult to perform spheroidization to meet the above size, so that the yield may decrease or the price may increase. In addition, the side reaction between the negative electrode active material particles and the electrolyte increases, resulting in a decrease in battery efficiency. On the other hand, when the negative electrode active material particles have a D of greater than 9.2 μm, the negative electrode active material particles have a D of greater than 9.2 μm. 50 When the flaky natural graphite particles constituting the natural graphite inside the negative electrode active material particles are large in size. When the flaky natural graphite particles having a large size become spherical natural graphite after the spheroidization process, there are too many interfaces inside the spherical natural graphite, and therefore, the internal stress is excessively increased. Therefore, during the charge and discharge of the battery, the volume of the negative electrode is excessively expanded, and the problem of battery life degradation may occur.
[0043] In terms of particle size distribution, the negative electrode active material particles may have a half width of 5.0 μm to 5.5 μm, specifically 5.2 μm to 5.4 μm, and more specifically 5.2 μm to 5.3 μm. When the half width is too small to be less than 5.0 μm, there is a problem of too low yield in the manufacturing process of the negative electrode active material particles. On the other hand, when the half width is greater than 5.5 μm, due to the uneven particle size distribution, the current cannot be uniformly transmitted in the negative electrode, thereby generating many parts where lithium precipitation is prone to occur, thereby deteriorating the fast charging performance of the battery. In addition, the negative electrode is over-expanded, so that the problem of battery life degradation may occur. When preparing the negative electrode active material particles, small-sized flaky natural graphite particles are used and a step of removing the internal pores of the spherical natural graphite is performed, thereby solving the problem of uneven size caused by the internal pores, and therefore, the half width can meet 5.5 μm or less. The half width corresponds to the horizontal axis width corresponding to the half value of the maximum vertical axis value of the highest peak in the particle size distribution.
[0044] In terms of particle size distribution, the D 90 / D 10 Can satisfy 1.5≤D 90 / D 10 ≤2.3, specifically 1.8≤D 90 / D 10 ≤2.3, more specifically 2.0≤D 90 / D 10 ≤2.3. Since the volume of the internal pores inside the negative electrode active material particles is at a low level, the above range can be met. When the above range is met, the particle size distribution becomes uniform, thereby improving the rapid charging of the battery.
[0045] The negative electrode active material may have 0.6 m 2 / g to 2.2m 2 / g, specifically 0.8m 2 / g to 2.1m2 / g, more specifically 0.9m 2 / g to 2.1m 2 / g of specific surface area. Since the volume of the internal pores inside the negative electrode active material particles is at a low level, the above range can be met. In other words, it is difficult to achieve the specific surface area only by forming a carbon coating on typical natural graphite or by controlling the shape of natural graphite (e.g., spherical). Since the technology of controlling the internal pores of natural graphite is accompanied by applying pressure to natural graphite, the specific surface area can be achieved. When the above range is met, the internal pores in the negative electrode active material particles are reduced, thereby reducing the side reactions between the negative electrode active material particles and the electrolyte and suppressing the excessive volume expansion of the negative electrode. Therefore, the life performance of the battery can be improved.
[0046] Specifically, when the specific surface area is less than 0.6 m 2 / g, since the internal pores and specific surface area of the negative electrode active material particles are greatly reduced, the interface resistance of the negative electrode during charging and discharging of the battery is excessively increased, and it is not conducive to the insertion / extraction of lithium ions, so that the fast charging performance is deteriorated and the capacity of the battery may be reduced. On the other hand, when the specific surface area is greater than 2.2m 2 / g, the side reaction between the negative electrode active material particles and the electrolyte increases, resulting in excessive expansion of the volume of the negative electrode during charge and discharge of the battery, so that the life of the battery may be shortened.
[0047] The pore volume of the negative electrode active material particles may be 1×10 -3 cm 3 / g to 14.8×10 -3 cm 3 / g, specifically 3×10 -3 cm 3 / g to 14×10 -3 cm 3 / g, more specifically 5×10 -3 cm 3 / g to 14×10 -3 cm 3 / g. Since the above range can be met due to the technology of applying pressure to natural graphite to control the internal pores of natural graphite. Therefore, the pore volume can be smaller than the pore volume of typical natural graphite to which such technology is not applied. When the above pore volume range is met, during the charge and discharge of the battery, the side reaction between the electrolyte and the negative electrode active material particles can be effectively suppressed and the volume expansion of the negative electrode active material particles can be suppressed, thereby improving the life performance of the battery.
[0048] The tap density of the negative electrode active material particles may be 1.00 g / cc to 1.20 g / cc, specifically 1.05 g / cc to 1.15 g / cc, more specifically 1.05 g / cc to 1.10 g / cc. When the above range is met, the shape of the negative electrode active material particles is spherical or nearly spherical, which means that the negative electrode adhesion can be improved.
[0049] The negative electrode may further include at least one of a binder and a conductive material.
[0050] The adhesive may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, materials in which hydrogen is replaced by Li, Na or Ca, and combinations thereof. In addition, the adhesive may include various copolymers thereof.
[0051] The conductive material is not particularly limited as long as it has conductivity without causing chemical changes in the battery. For example, graphite such as natural graphite or artificial graphite; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; conductive tubes such as carbon nanotubes; fluorocarbon powders; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. can be used.
[0052] <Method for manufacturing negative electrode>
[0053] Although not limited thereto, the negative electrode active material of the above embodiment may be prepared by the following method: The method may include preparing flaky natural graphite; modifying the flaky natural graphite into spherical natural graphite; forming a coating on the surface of the spherical natural graphite; and removing the internal pores of the spherical natural graphite.
[0054] When the flaky natural graphite is prepared, the size of the flaky natural graphite is smaller than that of general flaky natural graphite. Therefore, in the step of modifying the flaky natural graphite into spherical natural graphite, the size of the formed spherical natural graphite can be small.
[0055] When the flaky natural graphite is modified into the spherical natural graphite, the modification method can be performed by using, for example, a vortex mill.
[0056] The step of forming a coating on the surface of the spherical natural graphite can be performed by arranging a carbon precursor on the spherical natural graphite and heat treating it. The coating thus formed is the same as the carbon coating described in the above embodiment, and therefore, its description will be omitted. With the formation of the carbon coating, the specific surface area of the spherical natural graphite on which the carbon coating is formed can be further reduced.
[0057] In the step of removing the internal pores of the spherical natural graphite, the method for removing the internal pores may be cold isostatic pressing (CIP). Specifically, the spherical natural graphite having a carbon coating formed thereon is placed in a mold, and the mold is immersed in water. Afterwards, water is used as a medium to apply pressure to the mold having the spherical natural graphite having a carbon coating formed thereon. The pressure may be 85MPa to 95MPa, specifically 85MPa to 90MPa. The duration of the applied pressure may be 60 seconds to 120 seconds, specifically 90 seconds to 100 seconds. By the above method, isostatic pressing is applied to the spherical natural graphite having a carbon coating formed thereon, thereby removing the internal pores of the spherical natural graphite. Therefore, the specific surface area and internal pore volume of the prepared negative active material particles can be reduced. In addition, since the internal pores are removed, the particle size distribution of the negative active material particles can be adjusted, so that the half width range, D 50 Range, specific surface area range.
[0058] <Secondary Battery>
[0059] A secondary battery according to still another embodiment of the present invention may include a negative electrode, and the negative electrode may be the same as the negative electrode of the above-described embodiment.
[0060] Specifically, the secondary battery may include the negative electrode, the positive electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte. The negative electrode is the same as the above-mentioned negative electrode. Since the negative electrode has been described above, its detailed description will be omitted.
[0061] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.
[0062] In the positive electrode, the positive electrode collector is not particularly limited as long as it has conductivity without causing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode collector can generally have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the positive electrode collector to improve the adhesion of the positive electrode active material. For example, the positive electrode collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0063] The positive electrode active material may be a common positive electrode active material in the art. Specifically, the positive electrode active material may be a layered compound, such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2) or a compound replaced by one or more transition metals; lithium iron oxide, such as LiFe3O4; lithium manganese oxide, such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 and Cu2V2O7; LiNi 1-c2 M c2 O2 (wherein M is any one of Co, Mn, Al, Cu, Fe, Mg, B or Ga, and 0.01≤c2≤0.3) represented by Ni site type lithium nickel oxide; represented by the formula LiMn 2-c3 M c3 The positive electrode may be a lithium manganese composite oxide represented by the formula Li2Mn3MO8 (wherein M is any one of Co, Ni, Fe, Cr, Zn or Ta, and 0.01≤c3≤0.1) or Li2Mn3MO8 (wherein M is any one of Fe, Co, Ni, Cu or Zn); LiMn2O4 in which a part of Li in the formula is replaced by an alkaline earth metal ion, etc., but is not limited thereto. The positive electrode may be lithium metal.
[0064] The positive electrode active material layer may include a positive electrode conductive material and a positive electrode binder as well as the positive electrode active material.
[0065] At this time, the positive electrode conductive material is used to impart conductivity to the electrode, and any positive electrode conductive material can be used without particular limitation as long as it has electronic conductivity and does not cause chemical changes in the constituted battery. Specific examples thereof may include graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one of them or a mixture of two or more thereof may be used.
[0066] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Its specific examples may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, and any one or a mixture of two or more thereof can be used.
[0067] The separator is used to isolate the negative electrode from the positive electrode and provide a mobile path for lithium ions. Any separator can be used without particular limitation, as long as it is a separator commonly used in secondary batteries. In particular, a separator with excellent electrolyte moisture content and low resistance to ion movement in the electrolyte is preferred. Specifically, a porous polymer film can be used, for example, a porous polymer film made of polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure with more than two layers thereof. In addition, a typical porous non-woven fabric can be used, for example, a non-woven fabric formed by glass fibers or polyethylene terephthalate fibers with a high melting point as a separator. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator with a single layer or multilayer structure can be selectively used.
[0068] The electrolyte may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc., which may be used to prepare a lithium secondary battery, but is not limited thereto.
[0069] Specifically, the electrolyte may include a nonaqueous organic solvent and a lithium salt.
[0070] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate can be used.
[0071] Particularly, in carbonate organic solvents, ethylene carbonate and propylene carbonate as cyclic carbonates can be preferably used, because they are high viscosity organic solvents with high dielectric constant to dissociate lithium salts well. In addition, when such cyclic carbonates are mixed with linear carbonates (such as dimethyl carbonate and diethyl carbonate) with low viscosity and low dielectric constant in a suitable ratio, an electrolyte with high conductivity can be prepared, thereby the electrolyte can be more preferably used.
[0072] As the metal salt, a lithium salt can be used. The lithium salt is a material that is easily dissolved in a non-aqueous electrolyte. For example, as the anion of the lithium salt, a lithium salt selected from F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN -and (CF3CF2SO2)2N - One or more of the groups consisting of.
[0073] In the electrolyte, in order to improve the life performance of the battery, inhibit the reduction of the battery capacity and improve the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, one or more additives may be included, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum chloride, etc.
[0074] According to another embodiment of the present invention, a battery module including the secondary battery as a unit cell and a battery pack including the battery module are provided. The battery module and the battery pack include the secondary battery having high capacity, high rate performance and cycle performance, and thus can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems.
[0075] Hereinafter, the preferred embodiments of the present invention will be described in detail to facilitate understanding of the present invention. However, the embodiments are merely illustrative of the present invention, and therefore, it will be apparent to those skilled in the art that various modifications and variations may be made without departing from the scope and spirit of the present invention as disclosed in the appended claims. Obviously, these variations and modifications fall within the scope of the appended claims.
[0076] Examples and Comparative Examples
[0077] Example 1: Preparation of negative electrode
[0078] (1) Preparation of negative electrode slurry
[0079] As negative electrode active material particles (after a process for controlling internal pores (CIP)), particles containing spherical natural graphite particles formed by modifying flaky natural graphite and including a coating layer (accounting for 5 wt % in the negative electrode active material particles) disposed on the spherical natural graphite were used. In terms of particle size distribution measured by a particle size distribution meter (Microtrac S3500), the negative electrode active material particles had a D of 9.0 μm. 50 , 5.3 μm half width, 2.3 D90 / D10, 1.07 g / cc tap density and 14.0×10 -3 cm 3 / g pore volume.
[0080] The negative electrode active material particles, Super C65 as a conductive material, styrene-butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener were mixed at a weight ratio of 96.6:1:1.3:1.1, and then water was added to prepare a negative electrode slurry.
[0081] (2) Manufacturing of negative electrode
[0082] The negative electrode slurry was heated at 3.6 mAh / cm 2 A loading amount of 200 Å was applied on a copper foil (current collector), and then roll-pressed so that the negative electrode porosity became 28%, followed by vacuum drying at about 130° C. for 8 hours to manufacture the negative electrode of Example 1.
[0083] Example 2 and Comparative Examples 1 to 8: Preparation of Negative Electrode
[0084] A negative electrode was manufactured in the same manner as in Example 1 except that negative electrode active material particles as shown in Table 1 were used. Comparative Examples 1, 2, 4, and 7 were not subjected to the CIP process, and Comparative Example 7 was natural graphite in which pitch was intercalated.
[0085] [Table 1]
[0086]
[0087] In Table 1, D 10 , D 90 / D 10 The half width is a value determined on the particle size distribution derived by a particle size distribution meter (Microtrac S3500). In particular, the half width corresponds to the width of the horizontal axis corresponding to the half value of the maximum vertical axis value of the highest peak on the particle size distribution (see Figure 1 ). In Table 1, the tap density is a density calculated by placing 40 g of the negative electrode active material particles in a container and tapping it 1000 times. In Table 1, the pore volume and specific surface area are measured by a porosimetry analyzer (Bell Japan Co., Ltd., Belsorp-II mini).
[0088] Experimental Example 1: Confirmation of the volume expansion degree according to the charge / discharge cycle of the battery
[0089] Using the negative electrodes of each of Examples 1 and 2 and Comparative Examples 1 to 8, batteries were manufactured in the following manner.
[0090] As the positive electrode active material, LiCoO 2 was used. The positive electrode active material, carbon black as a conductive material, polyvinylidene fluoride (PVDF) as a binder were mixed at a weight ratio of 97.68:1.2:1.12 with N-methyl-2-pyrrolidone (NMP) as a solvent to prepare a positive electrode slurry.
[0091] The prepared positive electrode slurry was applied on an aluminum metal film having a thickness of 20 μm as a positive electrode current collector and then dried. At this time, the temperature of the circulating air was 110° C. Thereafter, the aluminum metal film to which the positive electrode slurry was applied and dried was rolled and then dried in a vacuum oven at 130° C. for 2 hours to manufacture a positive electrode including a positive electrode active material layer.
[0092] The negative electrode (the negative electrode of each of Example 1 and Comparative Examples 1 to 3), the manufactured positive electrode and the porous polyethylene separator are assembled using a stacking method, and an electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 2 / 8 (volume ratio), lithium hexafluorophosphate (1M LiPF6) and 0.5% vinylene carbonate (VC)) is injected into the assembled battery to manufacture a lithium secondary battery.
[0093] The secondary battery was charged / discharged under the following conditions to evaluate the volume expansion rate of the negative electrode after 30 cycles, and the results are shown in Table 2.
[0094] Volume expansion rate of negative electrode (%) = [(thickness of negative electrode after 30 cycles) / initial thickness of negative electrode] × 100
[0095] Charge / discharge conditions: at 25° C., charge and discharge were performed at 0.1 C in the 1st cycle, at 0.2 C in the 2nd cycle, and at 0.5 C for the 3rd to 30th cycles. After each charge and discharge, the rest time before the next cycle was set to 1 hour.
[0096] Charging conditions: CC-CV mode (4.35V, 0.05C voltage cutoff)
[0097] Discharge conditions: CC mode (2.75V voltage cut-off)
[0098] [Table 2]
[0099] Volume expansion rate (%) Example 1 22 Example 2 22 Comparative Example 1 27 Comparative Example 2 25 Comparative Example 3 27 Comparative Example 4 28 Comparative Example 5 27 Comparative Example 6 29 Comparative Example 7 30 Comparative Example 8 25
[0100] Referring to Table 2, it can be seen that the use of D 50 In the case of Examples 1 and 2 in which the negative electrode active material particles have the same or similar properties as those of the negative electrode active material particles of Example 1 and Example 2, the volume expansion rate of the negative electrode is low.
[0101] Experimental Example 2: Evaluation of the fast charging performance of the battery
[0102] Prepare to cut into 1.7671cm 2A circular lithium (Li) metal film was used as a positive electrode. A porous polyethylene separator was placed between the positive electrode and the negative electrode (the negative electrode of Example 1 and Comparative Example 1), and then an electrolyte was injected therein, wherein 0.5 wt% of vinylene carbonate was dissolved in a mixed solution in which ethyl methyl carbonate (EMC) and ethylene carbonate (EC) were mixed in a mixing volume ratio of 7:3, and LiPF6 was dissolved therein at a concentration of 1.0 M. Thereafter, it was left to stand for 24 hours to manufacture a lithium coin half-cell.
[0103] The manufactured half-cell was charged / discharged 3 times at 0.1C, and then the discharge capacity after the 3rd cycle was set as 1C reference. While charging in CC mode (3C) for 15 minutes, the output voltage according to the SOC change was shown in the graph (see Figure 2 ). In this figure, the X-axis shows SOC and the Y-axis shows the measured output voltage, and the fast charging performance was evaluated using a method of determining the Li plating SOC by finding the slope change point through the dV / dQ derivative.
[0104] Referring to Table 2, it can be seen that the use of D 50 In the case of Example 1 in which the negative electrode active material particles have 0.0447 W / m2 and 0.062 W / m2, the lithium deposition occurs with delay.
Claims
1. A negative electrode, comprising: Current collector; and A negative electrode active material layer, wherein The negative electrode active material layer comprises negative electrode active material particles, The negative electrode active material particles include natural graphite and a carbon coating layer disposed on the natural graphite, In terms of particle size distribution, the negative electrode active material particles have a D of 6 μm to 9.2 μm. 50 and a half width of 5.0 μm to 5.5 μm, and The specific surface area of the negative electrode active material particles is 0.6 m 2 / g to 2.2m 2 / g, In terms of particle size distribution, the negative electrode active material particles have a particle size distribution of 1.5≤D 90 / D 10 D ≤ 2.3 90 / D 10 .
2. The negative electrode according to claim 1, wherein in terms of particle size distribution, the negative electrode active material particles have a D 50 .
3. The negative electrode according to claim 1, wherein the specific surface area of the negative electrode active material particles is 0.8 m 2 / g to 2.1m 2 / g. 4 . The negative electrode according to claim 1 , wherein the natural graphite is natural graphite formed by aggregating flaky natural graphite particles. 5 . The negative electrode according to claim 1 , wherein the negative electrode active material particles have a tap density of 1.00 g / cc to 1.20 g / cc.
6. The negative electrode according to claim 1, wherein the pore volume of the negative electrode active material particles is 1×10 -3 cm 3 / g to 14.8×10 -3 cm 3 / g. 7 . The negative electrode according to claim 1 , wherein the carbon coating layer is contained in the negative electrode active material particles in an amount of 1 wt % to 15 wt %. 8 . The negative electrode according to claim 1 , wherein the carbon coating layer comprises at least any one of amorphous carbon and crystalline carbon. 9 . A secondary battery comprising the negative electrode according to claim 1 .
Citation Information
Patent Citations
How to Increase Omega-3 Polyunsaturated Fatty Acid Production in Microalgae
KR1020190004798A
Anode active material, anode comprising same, and lithium secondary battery
CN108140825A
Anode active material for lithium secondary battery and lithium secondary battery comprising the same
KR1020140132791A